Feline herpesvirus vectored-rabies vaccine in cats: A dual protection. Issue 16 (10th April 2019) - Chen, Teng; Zhou, Xintao; Qi, Yu; Mi, Lijuan; Sun, Xuefei; Zhang, Shoufeng; Liu, Ye; Olson, Victoria; Qiu, Wei; Wu, Xianfu; Hu, Rongliang
Abstract: In China, cats cause about 5% of human rabies cases. Rabies control in cats plays a role in achieving the ultimate goal of elimination of dog rabies-mediated human deaths. However, there is no cat-specific rabies vaccine in China yet. In this study, we constructed a recombinant rabies vaccine by using a felid herpesvirus 1 (FHV-1) isolate, and deleted the gI/E in the FHV-1 and replaced the region with a glycoprotein (G) of rabies virus (RABV) strain BD06 through homologous recombination. The recombinant virus FHV-RVG was recovered and purified, and the expression of RABV glycoprotein was verified by indirect immunofluorescent assay. For potency in cats, each animal was inoculated intranasally with 1 ml FHV-RVG at 10 6.5 TCID50 . Blood samples were collected at defined intervals for antibody titration. The animals were challenged by herpes and rabies after completion of vaccination on day 180 and day 194, respectively. Our results demonstrated all vaccinated cats generated antibodies against both FHV-1 and RABV, and reached an arbitrary protective titer > 0.5 IU/ml for rabies viral neutralizing antibody (VNA) by day 14 post inoculation (dpi) and titer peaked on 30 dpi with VNA at 24.5 ± 10.23 IU/ml. All vaccinated cats presented no clinical signs of FHV-1 infection and survived rabies challenge, while the control cats had severe rhinotracheitis and died from rabies after challenge. All this demonstrated that the FHV-based recombinant vaccine is effective in protection against both FHV-1 and RABV infections.